2005
DOI: 10.1002/cncr.21465
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for revision of the TNM classification system for renal cell carcinoma

Abstract: The authors thank Christine M. Lohse from the Division of Biostatistics, Mayo Clinic (Rochester, MN) for her excellent and kind collaboration with martingale residuals analysis. Receiving this kind of collaboration was a great honor for all the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 33 publications
0
31
0
2
Order By: Relevance
“…Such division was based on a study that showed the prognostic difference between tumors less than 4 cm and those greater than 4 cm [29]. This finding was also confirmed by a recent European multi-institutional study [30]. Another rationale for such division is that tumors less than 4 cm are amenable to nephron-sparing surgery.…”
Section: Tnm Stagingmentioning
confidence: 80%
“…Such division was based on a study that showed the prognostic difference between tumors less than 4 cm and those greater than 4 cm [29]. This finding was also confirmed by a recent European multi-institutional study [30]. Another rationale for such division is that tumors less than 4 cm are amenable to nephron-sparing surgery.…”
Section: Tnm Stagingmentioning
confidence: 80%
“…7,8 On revision, renal tumors were grossly stratified into <5.5 cm and >5.5 cm according to the new optimal tumor size breakpoint put forward by Ficarra et al, 9 and were classified according to the histologic and immunohistochemical criteria put forward by Eble et al in the WHO bluebook partially devoted to tumors of the urinary system and published in 2004. 10 We used the criteria put forward by Renshaw et al, 2 Grignon and Staerbel, 11 and Renshaw 12 for review of FNA smears.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all available mathematical models use the 1997 version of the TNM staging system that is very similar to the more recent 2002 version [32] . Nevertheless, it is possible to hypothesize that the forthcoming TNM version will satisfy some of the proposals for reclassification of organ-confined (T1-2), locally advanced (T3-4), and lymph node involving (N1-2) tumors published in the last years [33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%